Physico-mechanical properties and formaldehyde emission of rubberwood particleboard made with UF resin admixed with ammonium and aluminium-based hardeners - Abd Ghani, Muhammad Aizat; Bawon, Paiman; Lee, Seng Hua; Ashaari, Zaidon (Universiti Putra Malaysia Press, 2019)
In this study, the effects of addition of ammonium and aluminium-based hardeners into urea formaldehyde resin (UF) on the physico-mechanical properties and formaldehyde emission of the rubberwood particleboard were investigated. Four types of hardeners, namely ammonium chloride (AC), ammonium sulphate (AS), aluminium chloride (AlC) and aluminium sulphate (AlS), were added into UF resin. The acidity, gelation time, viscosity and free formaldehyde content of the UF/hardener mixtures were determined. Particleboard made with the UF/hardener mixtures were tested for physico-mechanical properties and formaldehyde emission. The pH values of the resin after addition of aluminium-based hardeners were higher and resulted in higher viscosity and shorter gelation time. Consequently, despite lower formaldehyde emission was recorded, the physico-mechanical properties of the resulted particleboard were inferior compared to that of ammonium-based hardeners. The best quality particleboard in terms of mechanical, physical and formaldehyde emission were obtained from the particleboard made with AS, followed by AC.